Rotavirus Associated Acute Gastroenteritis in the Pediatric Emergency Department: A Matched Case-control Study - Damla Hanalioğlu; Fatmanur Özbeyaz; Filiz Özdemir; Funda Kurt; İbrahim Yakut; Emine Dibek Mısırlıoğlu (Galenos Yayinevi, 2021)
Introduction:This study aimed to evaluate pediatric emergency department visits due to rotavirus- associated acute gastroenteritis by the means of laboratory parameters, length of stay at hospital, hospitalization rates and revisit rates in 72 hours after first admission.Methods:A matched case-control study was conducted. Pediatric patients under the age of 18 years who presented to the pediatric emergency department with acute diarrhea (three or more times/day) with/out vomiting between 1st January and 30th June 2018 were included. The study group was composed of patients who had positive stool rotavirus antigen test while the control group consisted of equal number of randomly selected age and gender matched patients whose stool rotavirus antigen tests were negative.Results:A total of 2.834 patients had stool rotavirus antigen test done. Stool rotavirus positivity was 5.3% (n=149). There was no difference between the groups according to age (2.5±2.0 year vs. 2.5±2.0 year, p=0.657) and gender (53% male vs. 55% male, p=0.816). Diarrhea and vomiting co-occurrence was significantly more frequent in the study group (87% vs. 55%, p<0.001). Dehydration symptoms were more common in the study group (57% vs. 27.5%, p<0.001). Differences between laboratory parameters such as pH (7.37±0.06 vs. 7.39±0.06, p=0.009), HCO3 (15.7±3.5 mmol/L vs. 17.4±3.5 mmol/L, p<0.001), BUN (31.9±16.0 mg/dL vs. 25.4±11.3 mg/dL, p<0.001) and uric acid (7.0±2.8 mg/dL vs. 5.7±2.5 mg/dL, p<0.001) were significant. Eight patients in the study group had co-infections with Adenovirus and/or amoeba. The study group had significantly longer hospital stay than the control group (12.3±14.2 hours vs. 7.6±10.4 hours, p=0.029). Hospitalization rates (38.9% vs. 18.1%, p<0.001) as well as revisit rates (14.1% vs. 5.4%, p=0.018) were also significantly higher in the study group.Conclusion:Vomiting, acute diarrhea and dehydration are leading symptoms of rotavirus gastroenteritis in childhood and rotavirus positivity is associated with longer hospital stay, higher hospitalization and revisit rates.